Performance Analysis of a Point Absorber Wave energy Converter in Nigerian West Coast; Gulf of Guinea - Kabiru Olayinka Oyegbemi; Orji U Charles; Douglas Ibiaba (International Journal of Marine Engineering Innovation and Research, 2023)
This paper presents a performance analysis of a point absorber wave energy converter (WEC) in the Gulf of Guinea along the Nigerian West Coast. The study aims to evaluate the device's efficiency and power output under different wave conditions in the Gulf, including extreme cases. To achieve this, an existing CAD model of a point absorber was reproduced in Auto-CAD and meshed in Ansys Aqua, to obtain the added mass and damping coefficient, it was finally imported in MATLAB where the simulation model was created using WEC-Sim software. The scatter diagram data from the region were analyzed, the probability of occurrence of each of the wave on the diagram was calculated and ranked, the top five conditions was fed in as input to the device. The results show that the device's efficiency is highest at a wave height of 2 meters and a peak period of 11 seconds. The power output is highest when the device resonates, this occur at a peak period and significant wave height of (4m & 15s). However, the efficiency decreases as power output increases. The study also confirms the device's suitability for the region, as it showed no abnormal behavior under extreme conditions. Further research is needed on optimizing the mooring line design and evaluating the cost-effectiveness of the device in the region.